2011
DOI: 10.1016/j.aquaculture.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Pathological manifestations of the acanthocephalan parasite, Tenuiproboscis sp. in the mangrove red snapper (Lutjanus argentimaculatus) (Forsskål, 1775), a candidate species for aquaculture from Southern India

Abstract: The study describes the pathological manifestations of the acanthocephalan, Tenuiproboscis sp. in the mangrove red snapper, Lutjanus argentimaculatus, a highly valued food fish along the southwest coast of India. The fish collected from Calicut, Cochin and Kannur harboured the acanthocephalan parasite, Tenuiproboscis sp. with up to 100% prevalence. Heavy infections with the parasites were observed in the posterior region of the intestine, almost blocking the lumen. At the site of parasite attachment, the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
3
25
1
1
Order By: Relevance
“…de Buron and Nickol (1994) reported occlusion and significant distention of caeca in Lepomis cyanellus infected with the acanthocephalan Leptorhynchoides thecatus (de Buron and Nickol, 1994). The Sclerocollum sp hooks at attachment sites have considerably damaged the tissue architecture of the host intestine leading to villi necrosis when compared to normal (Fig.5), same as observed by (Amin and Heckmann, 1992), fibroplasia extent to muscular mucosa similar lesion described by (de Buron and Nickol, 1994) and destroyed villi (Fig.11), this agree with (Sanil et al, 2010). Increase number of goblet cells, eosinophils aggregation and lymphocytes infilteration were stimulated by parasites infection has been well documented (Fig.7) as documented by (de Buron and Nickol, 1994;Thomas, 2002;Hamers et al, 1992 andDick andChoudhury, 2006).…”
Section: Histopathology Of Fish Intestine Infected With Sclerocollum Spsupporting
confidence: 79%
“…de Buron and Nickol (1994) reported occlusion and significant distention of caeca in Lepomis cyanellus infected with the acanthocephalan Leptorhynchoides thecatus (de Buron and Nickol, 1994). The Sclerocollum sp hooks at attachment sites have considerably damaged the tissue architecture of the host intestine leading to villi necrosis when compared to normal (Fig.5), same as observed by (Amin and Heckmann, 1992), fibroplasia extent to muscular mucosa similar lesion described by (de Buron and Nickol, 1994) and destroyed villi (Fig.11), this agree with (Sanil et al, 2010). Increase number of goblet cells, eosinophils aggregation and lymphocytes infilteration were stimulated by parasites infection has been well documented (Fig.7) as documented by (de Buron and Nickol, 1994;Thomas, 2002;Hamers et al, 1992 andDick andChoudhury, 2006).…”
Section: Histopathology Of Fish Intestine Infected With Sclerocollum Spsupporting
confidence: 79%
“…There are some reports of the genus Neoechinorhynchus from Indian marine fishes (Tripathi 1959;Chandra et al 1985) besides other acanthocephalan species, Serrasentis nadakali from Rachycentron canadum (George and Nadakal 1981) and Tenuiproboscis sp. in many marine fish species with aquaculture potential (Sanil et al 2011). The fishes were apparently healthy except choking of intestinal tract with several live acanthocephalan worms.…”
Section: Resultsmentioning
confidence: 96%
“…Again, the epidermal elevations at the base of hooks are absent in A. lucii. In Tenuiproboscis sp (Sanil et al 2011) observed a progressively decreasing size of hooks from anterior to posterior region, but the posterior most row of spines was larger. As in most acanthocephalan species, hook surface is smooth in E. veli in contrast to surface striations in Porrorchis indicus (Abd-El-Moaty and Taeleb, 2011), Dentitruneus truttae (Dezfuli et al 2008) and Rhadinorhynchus ornatus (Amin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Tenuiproboscis sp. neck is elongated (Sanil et al 2011). Rhadinorhynchus dorsoventrospinosus has a prominent neck with a posterior ring of hooks (Al Ghamdi 2013).…”
Section: Discussionmentioning
confidence: 99%